Updates on digital mental health interventions for children and young people: systematic overview of reviews. - Liverpool, Shaun; Mc Donagh, Ciarán; Feather, Julie; Uzondu, Chinebuli; Howarth, Michelle; Bannerman, Fariba; Kaehne, Axel; Foster, Celeste; Mateus, Ceu (European Child & Adolescent Psychiatry, 2025)
Digital mental health interventions (DMHIs) are increasingly recommended for children and young people (CYP) as a promising way to prevent and treat mental health problems. Here, we summarised and consolidated findings from existing systematic reviews to provide an overview of what is known, and which areas need further investigation. Systematic searches were conducted until January 2024 using PubMed, PsycINFO, MEDLINE, CINAHL, Scopus and Google Scholar. Records were screened against predefined criteria and quality assessed using A MeaSurement Tool to Assess Systematic Reviews (AMSTAR-2) and Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Systematic Reviews. A study protocol was co-developed with key stakeholders and registered on the Open Science Framework. From 941 records, 51 systematic reviews published between 2000 and 2023 of generally moderate quality, targeting CYP 0 to 25 years, were included in our narrative summary. DMHIs were delivered in a variety of ways, including online video calls, apps and various combinations, underpinned mostly by cognitive behaviour therapy. DMHIs supported different mental health problems, but mostly symptoms of anxiety and/or depression. Although generally effective, some studies reported mixed results with limited evidence when focusing on longer-term outcomes. Other benefits of DMHIs included reduced costs and time investments for families, and increased accessibility and acceptability of support. Practitioner preparedness and unclear ethics/safety measures were identified as factors impacting engagement and potential effectiveness. The findings suggest that DMHIs can be a valuable tool for supporting CYP. However, realising the full potential of DMHIs for all CYP may require more high-quality research utilising DMHIs that are diverse in theoretical underpinnings and target audiences.